PENGUJIAN TEGANGAN TEMBUS KABEL NYA INSTALASI LISTRIK TEGANGAN RENDAH - Ihwaldi Haris Bowta; Jumiati Ilham (Program Vokasi-Universitas Negeri Gorontalo, 2023)
This research examines the breakdown voltage on low voltage cables, by testing the voltage to breakdown and insulation resistance on low voltage cables. The purpose of this study was to determine the maximum limit of the cable sample's ability to receive injection voltage before experiencing an electric breakdown and the impact on insulation resistance and cable leakage current when given a voltage exceeding normal voltage and then to analyze the highest voltage that the cable can withstand in a certain time. The parameters used in the research design are insulation resistance and leakage current. The test was carried out at the High Voltage Laboratory, State University of Gorontalo with a high voltage tester HV transformer brand Terco Sweden with specifications for a maximum voltage capacity of up to 100 kV. The cable samples used were NYA 2x2.5 cables with the brands eterna, suprime and sigeru.